IMPLEMENTASI PERATURAN PRESIDEN NOMOR 54 TAHUN 2010 TENTANG PENGADAAN BARANG DAN JASA PEMERINTAH DI KABUPATEN SUKOHARJO - Yuli Isnandar; Hari Purwadi; I Gusti Ayu Ketut Rachmi Handayani (HUKUM PEMBANGUNAN EKONOMI, 2017)
AbstractThis article aims to describe the implementation of procurement auction policy of goods and services in Sukoharjo before and after the Presidential Regulation No. 54 of 2010 on Procurement of Government Goods and Services (e-procurement), to explain constraints in the implementation of procurement auction policy of goods and services in Kabupaten Sukoharjo after the issuance of Presidential Regulation No. 54 of 2010 on Procurement of Government Goods and Services (e-procurement) and its solution. This type of legal research is sociological or non-doctrinal with qualitative research methods that aim to know the Implementation of Presidential Regulation No. 54 of 2010 on Procurement of Government Goods and Services (Case Study of Implementation of E-Procurement in Sukoharjo District). Data collection techniques used interview techniques, literature study and documentation. The result of this research is in the implementation of the policy of auction of procurement of goods and services in Sukoharjo District before the Presidential Regulation Number 54 Year 2010 concerning Procurement of Government Goods and Services (e-procurement), there is Presidential Regulation Number 54 Year 2010 concerning Procurement of Government Goods and Services -procurement) in Sukoharjo Regency in accordance with Presidential Decree No. 80 of 2003 on Guidelines for Procurement of Government Goods and Services. Implementation of procurement auction policy of goods and services in Sukoharjo District after the Presidential Regulation Number 54 Year 2010 concerning Procurement of Government Goods and Services (e-procurement) that is, the length of time required in the procurement of goods/services in LPSE Sukoharjo District is 1) fiscal year. The time required to disseminate Presidential Regulation No. 54/2010 on Procurement of Goods/Services of the Government of Sukoharjo Regency is not maximal, since the socialization provided by the Sukoharjo District Government is very limited, since this socialization is only given the opportunity to the Official Commitment Officer/Procurement Committee and Civil Servants who are prepared as technical personnel managing goods/services Government that has a certificate Procurement of goods/services.Keywords: Procurement of goods and services; E-Procurement; LPSEAbstrakArtikel ini bertujuan untuk mendeskripsikan pelaksanaan kebijakan lelang pengadaan barang dan jasa di Kabupaten Sukoharjo sebelum dan sesudah adanya Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang dan Jasa Pemerintah (e-procurement), untuk menjelaskan kendala dalam pelaksanaan kebijakan  lelang pengadaan barang dan jasa di Kabupaten Sukoharjo setelah  adanya Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang dan Jasa Pemerintah (e-procurement) dan solusinya. Jenis penelitian hukum ini adalah sosiologis atau non doktrinal dengan metode penelitian kualitatif yang bertujuan untuk mengetahui  Implementasi Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang dan Jasa Pemerintah (Studi Kasus Pelaksanaan E-Procurement di Kabupaten Sukoharjo). Teknik pengumpulan data menggunakan teknik wawancara, studi kepustakaan dan dokumentasi. Hasil penelitian ini adalah dalam pelaksanaan kebijakan lelang pengadaan barang dan jasa di Kabupaten Sukoharjo sebelum adanya Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang dan Jasa Pemerintah (e-procurement), terdapat Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang dan Jasa Pemerintah (e-procurement) di Kabupaten Sukoharjo sesuai dengan Keputusan Presiden Nomor 80 Tahun 2003 TentangPedoman Pelaksanaan Pengadaan Barang dan Jasa Pemerintah. Pelaksanaan kebijakan lelang pengadaan barang dan jasa di Kabupaten Sukoharjo setelah  adanya Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan Barang dan Jasa Pemerintah (e-procurement) yaitu, lamanya waktu yang dibutuhkan dalam pelaksanaan pengadaan barang/jasa di di LPSE Kabupaten Sukoharjo adalah 1 (satu) tahun anggaran. Waktu yang dibutuhkan dalam melakukan sosialisasi Peraturan Presiden Nomor 54 Tahun 2010 tentang Pengadaan barang/jasa Pemerintah untuk Kabupaten Sukoharjo tidaklah maksimal, karena sosialisasi yang diberikan oleh Pemerintah Kabupaten Sukoharjo sangatlah dibatasi, karena sosialisasi ini hanya diberikan kesempatan kepada Pejabat Pembuat Komitmen Pejabat/Panitia Pengadaan dan Pegawai Negeri Sipil yang dipersiapkan sebagai tenaga teknis pengelola barang/jasa Pemerintah yang telah memiliki sertifikat Pengadaan barang/jasa. Kata Kunci: Pengadaan barang dan jasa; E-Procurement; LPSE